Gothic Healing under the Mediterranean Sun: “The Magus” by John Fowles as a Gothic Novel - Kowalcze, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The present paper aims at interpreting the novel “The Magus” by John Fowles within the framework of the Gothic genre. The argument shall be founded on a close analysis of chosen characteristics of the Gothic convention which can be identified within the text, such as the theatricality, the motif of insanity, as well as the issue of repressed sexuality. It shall also be argued that the novel presents the therapeutic role of fear, intrinsically linked to the Gothic mode of expression. The boundary between the rational and the irrational is suspended to the point that the protagonist is unable to tell whether the apparitions he sees in the Magus’s shadowy estate are of supernatural provenance or they constitute mere figments of his imagination deluded by the elements of the Mediterranean ambience. Remarkably, it is the experience of terror that ultimately heals Nicholas, an embittered and disillusioned young man, from the state of apathy and emotional handicap.

Celem niniejszego artykułu jest próba interpretacji powieści Johna Fowlesa „Mag” pod kątem obecnych w niej motywów gotyckich. Analizie poddane zostaną takie elementy konwencji gotyckiej jak: teatralność wydarzeń, motyw szaleństwa czy kwestia tłumionej seksualności. Autorka pragnie zwrócić uwagę na nieodzowny dla stylu gotyckiego element lęku, który w powieści pełni funkcję terapeutyczną. W powieści granica pomiędzy racjonalnym i irracjonalnym zostaje zatarta do tego stopnia, że główny bohater nie jest w stanie stwierdzić, czy wydarzenia, które mają miejsce w mrocznym domostwie tytułowego maga, dzieją się w rzeczywistości, czy też są dziełem jego omamionej śródziemnomorską rzeczywistością wyobraźni. Towarzyszący doświadczeniom Nicholasa strach ostatecznie uzdrawia zgorzkniałego mężczyznę ze stanu apatii i upośledzenia emocjonalnego.
Gotyckie uzdrowienie w śródziemnomorskim słońcu. „Mag” Johna Fowlesa jako powieść gotycka
Keywords: outcast; emotional handicap; psychic make-up; illusion; Gothic; wyrzutek; irracjonalność; dysfunkcja emocjonalna; konstytucja psychiczna; gotyk